Secondary metabolites from Micromonospora ectrinospora G017 - Quyen, Vu Thi; Ngan, Truong Bich; Mai Huong, Doan Thi; Bourguet Kondracki, Marie-Lise; Longeon, Arlette; Murphy, Brian Murphy; Minh, Chau Van; Cuong, Pham Van (Vietnam Journal of Chemistry, 2015)
Eight compounds, cyclo-(Pro-Tryp) (1), N-[2-(1H-indol-3-yl)-2-oxo-ethyl] acetamide (2), cyclo-(Pro-Tyr) (3), cyclo-(Pro-Phe) (4), cyclo-trans-4-OH-(Pro-Phe) (5), cyclo-(Pro-Leu) (6), cyclo-(Pro-Val) (7), and uracil (8) were isolated from the culture broth of the marine Micromonospora ectrinospora G017 strain. The structures of the isolated compounds were established on the basis of their spectral data, including mass spectrometry and NMR.